IPSILATERAL INJURIES OF THE ELBOW JOINT AND THE DISTAL RADIUS - Matelenok, Ievgen (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The elbow joint injury and the ipsilateral fractures of distal radius are rare but are different. Objective. To analyze character of the elbow joint injury and distal part radius fractures in connection with peculiarities of traumatic energy intensity, to consider of treatment options of such trauma cases. Methods. The study is based on the retrospective analyze of the clinical observation of 8 patients with the ipsilateral elbow joint injury and distal part of radius (3 men and 5 women, average age is 39 ± 5). Besides of the distal part radius fracture 1 patient had luxation of the forearm, 5 — fracture-dislocations in the elbow joint and in 2 cases — the fractures of distal metaepiphysis of the humerus. In 7 cases of the elbow joint injuries and in 3 cases of the distal part radius fractures the surgical treatment was made. Results. Except 2 cases the injuries happened in result of landing from the height of 1–12 meters. The severity of injuries was ranking and their correlation with the indicator of falling height was analyzed. The treatment peculiarity of the elbow joint injury and the ipsilateral fractures of distal part radius is considered. Conclusions. In the majority of cases ipsilateral injuries of the elbow joint and of the distal part radius are the result of falling from the height, infrequently — the results of falling from easy posture of the body; the severity of injury depends on the falling height (correlation coefficient Spearman’s — 0.78), the character of elbow joint injury may depend on the position of the extremity at the time of landing and successive additional collision of elbow region with traumatic agent. When the patient falls from significant height may happen polytrauma, what lead to many stages of treatment. By the ipsilateral injuries substantiation of manipulations or surgical operations priorities is very important.